Measurements and source apportionment of particle-associated polycyclic aromatic hydrocarbons in ambient air in Riyadh, Saudi Arabia. (July 2016) - Bian, Qijing; Alharbi, Badr; Collett, Jeffrey; Kreidenweis, Sonia; Pasha, Mohammad J.
Abstract: Ambient air samples were obtained in Riyadh, the capital and largest city of Saudi Arabia, during two measurement campaigns spanning September 2011 to September 2012. Sixteen particle-phase polycyclic aromatic hydrocarbons (PAH) were quantified in 167 samples. Pyrene and fluoranthene were the most abundant PAH, with average of 3.37 ± 14.01 ng m −3 and 8.00 ± 44.09 ng m −3, respectively. A dominant contribution from low molecular weight (LMW) PAH (MW < 228) suggested a large influence of industrial emissions on PAH concentrations. Monte Carlo source apportionment using diagnostic ratios showed that 80 ± 10% of the average LMW PAH concentrations were contributed by petroleum vapor emissions, while 53 ± 19% of high molecular weight (HMW) PAH were from solid fuel combustion emissions. The positive matrix factorization model estimated that oil combustion emissions dominated total PAH concentrations, accounting for on average 96%, likely due to widespread use of oil fuels in energy production (power plants and industries). Our results demonstrate the significant influence of petroleum product production and consumption on particulate-phase PAH concentrations in Riyadh, but also point to the importance of traffic and solid fuel burning, including coke burning and seasonal biomass burning, especially as they contribute to the ambient levels of HMW PAH. Highlights: One year of particle-phase PAH concentration measurements in Riyadh are reported. High concentrations of low-molecular-weight (LMW) PAH were observed. LMW PAH were attributed to evaporative and oil combustion sources. A unique source profile was associated with energy production from oil combustion. High-molecular-weight PAH were associated with traffic and solid fuel combustion.